Mediation Assistance for Domestic Conflicts Based on Legal and Religious Values in Overcoming Economic Conflicts and Infidelity in the Community of Batu City - Dwi Ari Kurniawati; Diyan Isnaen; Dzulfikar Rodafi (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
The issue addressed in this community service program is the high rate of domestic conflict in Batu City, particularly that caused by economic problems and infidelity, as well as the lack of local mediators capable of handling these cases with a comprehensive, appropriate approach to the community's socio-cultural context. This community service focuses on three main points: (1) Assistance in mediating domestic economic conflicts through the integration of family law and religious ethics; (2) Assistance in domestic reconciliation after infidelity based on legal justice and religious moral values; (3) Capacity building for family mediators with legal and religious knowledge. The method used is Participatory Action Research (PAR), in which the service team collaboratively designs programs, provides direct assistance, and trains prospective mediators together with partners and community members in Batu City. The entire process involves beneficiaries actively participating in identifying needs, implementing activities, and evaluating results, ensuring that the interventions carried out are truly contextual and sustainable. The results of community services show success in three aspects. First, establishing an effective hybrid mediation model to resolve economic conflicts by combining legal certainty with spiritual peace. Second, the integrated legal-religious approach succeeded in opening a space for constructive dialogue for reconciliation or a more dignified separation in cases of infidelity. Third, the formation of a cadre of competent local family mediators who understand substantive law and are sensitive to religious values, ready to become agents of sustainable peace in their communities.